Pengetahuan dan Sikap Petugas Taruna Siaga Bencana dalam Pencegahan Kebakaran - Ramli, Rahmat; Achmad, Viyan Septiyana; Mahoklory, Serly Sani; Nurhaedah, Nurhaedah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Factors that affect the level of preparedness of an officer are years of service, level of knowledge, and preparedness training. The working period of an officer affects the level of preparedness of an officer. Officers who work longer have a better level of preparedness 3 than new officers. The level of knowledge also influences the officer's preparedness efforts, a person's level of preparedness can be formed by how often the person gets knowledge or information regarding prevention and preparedness. Preparedness training held in a company also affects the level of preparedness when a fire disaster occurs, officers who take part in training have better preparedness than officers who do not take part in training. The aim of the study was to describe the level of knowledge and attitudes of cadets responding to disasters in a fire disaster. This study uses a descriptive research method using a cross-sectional approach which is a study of several populations observed at the same time (Nursalam, 2017). By distributing questionnaires to research respondents, with the intention of knowing the description of the knowledge and attitudes of disaster cadet response officers in handling fire disaster preparedness in the province of South Sulawesi.